Optimized heparin adsorption using macroporous zeolites: A comprehensive study - Katelyn R. Reid; Alireza Tabibi; Parisa Adami; Benson Karimi (Heliyon)
Heparin is a highly valuable active pharmaceutical ingredient, typically derived from porcine intestinal mucosa. Traditionally, various commercial resins have been used as adsorbents for heparin extraction; however, there has been growing interest in exploring more cost-effective adsorbents in recent years to improve heparin recovery. Zeolites, a typical aluminosilicate known for their high surface area, porosity, and thermal stability, were selected for evaluation in this study. We investigated the performance of two different zeolites, CBV901 and CBV10A, in recovering heparin. Our findings indicate that the CBV901 zeolite exhibits excellent efficiency (44 %) along with capacity (23.3 mg.g-1) for adsorption when used with porcine intestinal mucosa. A mechanistic analysis using kinetic and thermodynamic models revealed that the surface conditions were favorable for heparin adsorption. Additionally, we examined the effects of various conditions including adsorption time, as well as sorbent reusability for recovery process refinement.